Expression of Flavone Synthase II and Flavonoid 3′-Hydroxylase Is Associated with Color Variation in Tan-Colored Injured Leaves of Sorghum - Mizuno, Hiroshi; Yazawa, Takayuki; Kasuga, Shigemitsu; Sawada, Yuji; Kanamori, Hiroyuki; Ogo, Yuko; Hirai, Masami Yokota; Matsumoto, Takashi; Kawahigashi, Hiroyuki (Frontiers in Plant Science, 2016)
Sorghum (Sorghum bicolor L. Moench) exhibits various color changes in injured leaves in response to cutting stress. Here, we aimed to identify key genes for the light brown and dark brown color variations in tan-colored injured leaves of sorghum. For this purpose, sorghum M36001 (light brown injured leaves), Nakei-MS3B (purple), and a progeny, #7 (dark brown), from Nakei-MS3B × M36001, were used. Accumulated pigments were detected by using high-performance liquid chromatography: M36001 accumulated only apigenin in its light brown leaves; #7 accumulated both luteolin and a small amount of apigenin in its dark brown leaves, and Nakei-MS3B accumulated 3-deoxyanthocyanidins (apigeninidin and luteolinidin) in its purple leaves. Apigenin or luteolin glucoside derivatives were also accumulated, in different proportions. Differentially expressed genes before and after cutting stress were identified by using RNA-seq. Integration of our metabolic and RNA-seq analyses suggested that expression of only flavone synthase II (FNSII) led to the synthesis of apigenin in M36001, expression of both FNSII and flavonoid 3′-hydroxylase (F3′H) led to the synthesis of apigenin and luteolin in #7, and expression of both flavanone 4-reductase and F3’H led to the synthesis of 3-deoxyanthocyanidins in Nakei-MS3B. These results suggest that expression of FNSII is related to the synthesis of flavones (apigenin and luteolin) and the expression level of F3′H is related to the balance of apigenin and luteolin. Expression of FNSII and F3′H is thus associated with dark or light brown coloration in tan-colored injured leaves of sorghum.